Survival virulent characteristics and transcriptomic analyses of Vibrio mimicus exposed to starvation - Jiang, Ziyan; Gu, Shuwen; Qian, Qieqi; Li, Jie; Ji, Peng; Wu, Congcong; Zhang, Yingjie; Gao, Xiaojian; Jiang, Qun; Zhang, Xiaojun (Frontiers in Marine Science, 2022)
Vibrio mimicus is a global causative agent of vibriosis in a variety of aquatic animals and causes major economic losses to aquaculture. It could survive in water for extended periods of time under environmental stress, but its survival strategy remains unknow. This study described the survival, virulent and gene expression changes of V. mimicus cells undergoing starvation stress. After 4 weeks’ cultivation in media without nutrients, V. mimicus Y4 showed reduced rates of activity with marked changes in morphology and physiological activities. The culturable cell counts declined gradually to 104 CFU/mL and the shape changed from rod-shaped to coccoid with short rods or spherical. The motility of starved cells decreased after starvation and the biofilm production was significantly lower than wild cells. The starved cells still produced β-hemolysis, lecithinase and caseinase, but its infectivity to Macrobrachium nipponense was weakened. To investigate the mechanism behind morphological and physiological changes, we further analyzed differently expressed genes (DEGs) between starved and wild cells at the whole transcriptional level. The RNA-seq analysis demonstrated that large-scale DEGs were involved in transferase, membrane, dehydrogenase, synthase, flagellar, hemolysin, pilus assembly, and starvation, etc. Among them, the well-known virulence-related genes were downregulated significantly, including vmh, pilA, vipA, capB, tadC, huvX, ompA, etc. These data provide a key resource to understand the regulatory mechanisms of V. mimicus to starvation stress.